2008
DOI: 10.1007/s11146-008-9141-3
|View full text |Cite
|
Sign up to set email alerts
|

Flood Hazards and Urban Housing Markets: The Effects of Katrina on New Orleans

Abstract: Housing markets, Hedonic estimation, Flooding, Elevation, Housing supply, Katrina,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Montz (1987) theorized that the impact of SFHA designation on property value may be negatively related to the amount of time since the last flood. Support for this theory has been provided by, among others, Speyrer and Ragas (1991); Bin and Polasky (2004); Kousky (2010) and McKenzie and Levendis (2010) all report that price impacts on single-family houses in a SFHA tend to be larger after a flood occurs compared to beforehand. Therefore, the low discount discovered in the present study may be due to the fact that the last catastrophic flood in the study area occurred approximately a century ago and the last local flood that resulted in a Presidential disaster declaration occurred during the second year of our 23 year study period; 1989 (causing only $4.3 million in damage; an inconsequential number compared to the damage caused in other flood studies).…”
Section: Resultsmentioning
confidence: 92%
“…Montz (1987) theorized that the impact of SFHA designation on property value may be negatively related to the amount of time since the last flood. Support for this theory has been provided by, among others, Speyrer and Ragas (1991); Bin and Polasky (2004); Kousky (2010) and McKenzie and Levendis (2010) all report that price impacts on single-family houses in a SFHA tend to be larger after a flood occurs compared to beforehand. Therefore, the low discount discovered in the present study may be due to the fact that the last catastrophic flood in the study area occurred approximately a century ago and the last local flood that resulted in a Presidential disaster declaration occurred during the second year of our 23 year study period; 1989 (causing only $4.3 million in damage; an inconsequential number compared to the damage caused in other flood studies).…”
Section: Resultsmentioning
confidence: 92%
“…If the flood caused updating of risks that upset the market equilibrium, but transaction costs of moving were high, the coefficients estimated here will be lower than if homeowners could costlessly relocate after the fiood. It has been found that elevated homes in flood prone areas of New Orleans command a price premium and that this premium increased after Hurricane Katrina (McKenzie and Levendis 2008). To test for such postdisaster effects in St. Louis County, I interacted the elevation variable with the postfiood and the 100-year floodplain variables (not reported; available from the author).…”
Section: Ffect Of the ¡993 Floodmentioning
confidence: 99%
“…The results show that higher elevations have higher property values, indicating that there may be some variation of flood risk and housing prices within the 100‐year flood plain. McKenzie and Levendix (2010) use pre‐ and post‐hurricane Katrina data and similarly conclude that homes with higher elevation command a premium over lower elevation homes in New Orleans. Their results also indicate that Katrina increased the premium for higher elevation homes, suggesting a greater flood risk discount for frequent or recent events.…”
mentioning
confidence: 95%